Pembrolizumab plus chemotherapy for advanced and recurrent cervical cancer: final analysis according to bevacizumab use in the randomized KEYNOTE-826 study - Lorusso, D (2024)
Background: In KEYNOTE-826 (NCT03635567), pembrolizumab plus chemotherapy (±bevacizumab) significantly improved overall survival (OS) and progression-free survival (PFS) in patients with persistent, recurrent, or metastatic cervical cancer. This exploratory analysis examined outcomes in patient subgroups defined by bevacizumab use. Patients and methods: Eligible adult patients had persistent, recurrent, or metastatic squamous cell carcinoma, adenosquamous carcinoma, or adenocarcinoma of the cervix not previously treated with chemotherapy and not amenable to curative treatment; measurable disease per RECIST v1.1; and an Eastern Cooperative Oncology Group performance status ≤1. Patients were randomly allocated 1: 1 to pembrolizumab 200 mg every 3 weeks or placebo for up to 35 cycles plus chemotherapy (±bevacizumab 15 mg/kg). Dual primary endpoints were OS and PFS per RECIST v1.1 by investigator assessment. Outcomes were assessed in subgroups defined by bevacizumab use. Hazard ratios (HRs) and 95% confidence intervals (CIs) were based on a stratified Cox regression model. Results: A total of 617 patients were randomly assigned [pembrolizumab arm, n = 308 (63.6% with bevacizumab); placebo arm, n = 309 (62.5% with bevacizumab)]. The most common reason for bevacizumab exclusion was medical contraindication (75.9%). Among patients who received bevacizumab, HRs (95% CIs) for PFS favored the pembrolizumab arm in the programmed cell death-ligand 1 combined positive score ≥1 [0.56 (0.43-0.73)] and all-comer [0.57 (0.45-0.73)] populations; OS results were 0.60 (0.45-0.79) and 0.61 (0.47-0.80), respectively. Among patients who did not receive bevacizumab, HRs (95% CIs) for PFS also favored the pembrolizumab arm in the programmed cell death-ligand 1 combined positive score ≥1 [0.61 (0.44-0.85)] and all-comer [0.69 (0.50-0.94)] populations; OS results were 0.61 (0.44-0.85) and 0.67 (0.49-0.91), respectively. Among patients who received bevacizumab, grade ≥3 treatment-related adverse events occurred in 74.0% of patients in the pembrolizumab arm and 66.8% in the placebo arm. Conclusion: Pembrolizumab plus chemotherapy prolonged PFS and OS and had manageable safety compared with placebo plus chemotherapy in patient subgroups defined by bevacizumab use.